"Need, Design, and Development of Educational Software for Basic Ophthalmology Learning in Medical Students" - Pérez-Martinot , Manuel (2025)
The importance of adopting information and communication technologies in medical education is highlighted, as is the need to develop educational software (ES) to teach basic ophthalmology to medical students. Objectives: To determine the need to develop ES for learning basic ophthalmology and to design and develop the educational software. Methods: An operational research study was conducted in three stages: needs assessment, design, and development of the ES. A bibliographic search was conducted in the MEDLINE/PubMed, Scopus, and LILACS databases, and the ophthalmology curricula for medical students from four Peruvian universities were reviewed. Following this, the design method was explained and justified. Results: It was found that, worldwide, there are limited and isolated experiences with ES related to ophthalmology teaching, and no reported experiences in Peru. The time allocated for learning ophthalmology in the curricula averaged two theoretical class sessions, three clinical practice sessions, and one laboratory session. The ES was well justified and detailed, based on its thematic content and presentation format. Conclusions: The need for the designed ES with ophthalmology content for undergraduate medical education was identified. The development of ophthalmology ES aimed at medical students is essential as a didactic educational support resource.